Impact of Corruption on V4 Countries Economic Growth - Linhartová, Veronika; Stejskal, Jan (Vysoká škola báňská-Technická univerzita Ostrava, 2017)
Corruption is a serious problem the society faces since time immemorial. It is a problem that is persistent and very widespread; despite this, it cannot be solved either very easily or successfully. The academic literature, however, finds different effects of corruption on economic performance. Some studies describe how corruption „greases the wheels” of economy by overcoming bureaucratic constraints, inefficient provision of public services and rigid laws. Other studies argue that corruption only reduces economic performance. Based on the searches results of the theoretical literature and empirical studies, this contribution verificates the validity of hypotheses about the negative impact of corruption on economic growth of V4 countries in the period 1999 - 2015. The validity of the hypothesis of corruption’s negative influence was verified on a panel data sample. The validity of the hypothesis of corruption’s negative influence on economic growth for V4 countries was confirmed. Corruption negatively influences economic growth directly but also indirectly via transmission channels in V4 countries.
Vliv korupce na ekonomický růst zemí V4
Keywords: Corruption; economic growth; V4 countries; post-communist countries.; Korupce; hospodářský růst; státy V4; postkomunistické státy.